(untitled) (World Economics and Finance Bulletin, 2023)
Commercial banks are important players in the country’s financial system. Due to the country’s rapid development, various problems have been identified in the area of internal control and risk management. This has prompted people to pay more attention to the issue. They are hoping that the banks can improve their internal control systems and prevent potential risks. The goal of this study is to analyze the internal control framework of Iraq’s commercial banks. It uses the five elements of the COSO framework to identify the key factors that can affect the bank’s operations and risk management. Through a comprehensive analysis of the bank’s control environment, we can identify the areas where we can improve the system